The Effect of Casting Mold Material on Microstructure of Al-Si Alloys - Vlach, Tomas; Cais, Jaromir (Manufacturing Technology Journal, 2022)
This article deals with the influence of the mold material on the segregation process in selected Al-Si alloys. Three types of Al-Si alloys were chosen in order to compare the segregation process while congealing. AlSi7Mg0.3, AlSi7Cu4 and AlSi10.5Cu1.2Mn0.8Ni1.2Pb0.5 alloys were cast by gravity casting in a metal and sand molds. Macroscopic and microscopic analysis of the internal structure of each of the alloys was also studied. The chemical composition within the lower, middle and upper parts of the casts were observe by using scanning electron microscope. All samples were subjected to the Vickers microhardness measurement of a solid solution of α(Al). The distance between the secondary axes of the dendrites DAS (Dendrite Arm Spacing) was used to evaluate the level of segregation.
Keywords: Segregation; Heterogeinity; Aluminium alloys; Microstructure; DAS; Microhardness